The Protective Effect of Anthocyanins Extracted from Aronia Melanocarpa Berry in Renal Ischemia-Reperfusion Injury in Mice - Li Li; Jun Li; Hui Xu; Fengmei Zhu; Zhijun Li; Hongzhi Lu; Jinrong Zhang; Zhengsheng Yang; Yongsheng Liu (Mediators of Inflammation)
Background. Our previous research showed the antioxidant activity of anthocyanins extracted from Aronia melanocarpa of black chokeberry in vitro. Ischemia acute kidney injury is a significant risk in developing progressive and deterioration of renal function leading to clinic chronic kidney disease. There were many attempts to protect the kidney against this progression of renal damage. Current study was designed to examine the effect of pretreatment with three anthocyanins named cyanidin-3-arabinoside, cyanidin-3-glucodise, and cyaniding-3-galactoside against acute ischemia-reperfusion injury in mouse kidney. Methods. Acute renal injury model was initiated by 30 min clamping bilateral renal pedicle and followed by 24-hour reperfusion in C57Bl/6J mice. Four groups of mice were orally pretreated in 50 mg/g/12 h for two weeks with cyanidin-3-arabinoside, cyanidin-3-glucodise, and cyaniding-3-galactoside and anthocyanins (three-cyanidin mixture), respectively, sham-control group and the renal injury-untreated groups only with saline. Results. The model resulted in renal dysfunction with high serum creatinine, blood urea nitrogen, and changes in proinflammatory cytokines (TNF-ɑ, IL-1β, IL-6, and MCP-1), renal oxidative stress (SOD, GSH, and CAT), lipid peroxidation (TBARS and MDA), and apoptosis (caspase-9). Pretreatment of two weeks resulted in different extent amelioration of renal dysfunction and tubular damage and suppression of proinflammatory cytokines, oxidative stress, lipid peroxidation, and apoptosis, thus suggesting that cyanidins are potentially effective in acute renal ischemia by the decrease of inflammation, oxidative stress, and lipid peroxidation, as well as apoptosis. Conclusion. the current study provided the first attempt to investigate the role of anthocyanins purified from Aronia melanocarpa berry in amelioration of acute renal failure via antioxidant and cytoprotective effects.